The Partitioning of Newly Assimilated Linoleic and α-Linolenic Acids Between Synthesis of Longer-Chain Polyunsaturated Fatty Acids and Hydroxyoctadecaenoic Acids Is a Putative Branch Point in T-Cell Essential Fatty Acid Metabolism - von Gerichten, Johanna; West, Annette L.; Irvine, Nicola A.; Miles, Elizabeth A.; Calder, Philip C.; Lillycrop, Karen A.; Fielding, Barbara A.; Burdge, Graham C. (Frontiers in Immunology, 2021)
Longer chain polyunsaturated fatty acids (LCPUFA) ≥ 20 carbons long are required for leukocyte function. These can be obtained from the diet, but there is some evidence that leukocytes can convert essential fatty acids (EFA) into LCPUFA. We used stable isotope tracers to investigate LCPUFA biosynthesis, and the effect of different EFA substrate ratios, in human T lymphocytes. CD3+ T cells were incubated for up to 48 hours with or without concanavalin A in media containing a 18:2n-6 : 18:3n-3 (EFA) ratio of either 5:1 or 8:1, and [13C]18:3n-3 plus [d5]18:2n-6. Mitogen stimulation increased the amounts of 16:1n 7, 18:1n 9, 18:2n 6, 20:3n 6, 20:4n 6, 18:3n 3 and 20:5n 3 in T cells. Expression of the activation marker CD69 preceded increased FADS2 and FADS1 mRNA expression, and increased amounts of [d5]20:2n 6 and [13C]20:3n 3 at 48 hours. 22 carbon n 6 or n 3 LCPUFA synthesis was not detected, consistent with the absence of ELOVL2 expression. An EFA ratio of 8:1 reduced 18:3n 3 conversion and enhanced 20:2n 6 synthesis compared to a 5:1 ratio. [d5]9- and [d5]-13-hydroxyoctadecadienoic (HODE) and [13C]9- and [13C]13-hydroxyoctadecatrienoic acids (HOTrE) were the major labelled oxylipins in culture supernatants; labelled oxylipins ≥ 20 carbons were not detected. An EFA ratio of 8:1 suppressed 9- and 13-HOTrE synthesis, but there was no significant effect on 9- and 13-HODE synthesis. These findings suggest that partitioning of newly assimilated EFA between LCPUFA synthesis and hydroxyoctadecaenoic acid may be a metabolic branch point in T cell EFA metabolism that has implications for understanding the effects of dietary fats on T lymphocyte function.